Le rendement des obligations provinciales et l’incertitude politique : une analyse de séries chronologiques - Montmarquette, Claude; Dallaire, Claude (L'Actualité économique)

(untitled) (HEC Montréal, 1980)
AbstractIn this text, we apply time series techniques (Box-Tiao) to isolate the influence of the Parti québécois' electoral win of November 1976 on the financial and economic costs of the Québec government borrowings.For long term bonds issue between November 1976 and February 1979, we estimated at 32.49 millions of $ at 1979 present value or 1.22% of the total amount borrowed, the supplementary financial cost. In terms of additional payments to non-Québécois holding Québec government bonds, this associated economic cost has been evaluated at 11.21 millions of $ at 1979 present value, representing .42% of total borrowings. These costs may vary with respect to inflation and exchange rates and it must be emphasized that they are based on the evolution of yield differentials between Québec and Ontario government bonds and not on their direct yields to maturity. In that respect, these supplementary costs are only relative to the situation of Ontario and it is not impossible that the Parti québécois' électoral win have displaced the lenders portfolios of Canadian provincial bonds to the benefit of the government of Ontario.Finally, approximately two years and half following the pequist victory, the financial markets have retrieved to their former structure.